2014
DOI: 10.4314/ajtcam.v11i4.9
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory activity of the extracts of popular medicinal herbs on CYP1A2, 2C9, 2C19 and 3A4 and the implications for herb-drug interaction

Abstract: Background: Studies have suggested an increasing practice of concurrent herb-drug consumption. One of the major clinical risks of such concomitant herb-drug use is pharmacokinetic herb-drug interaction (HDI). This is brought about by the ability of phytochemicals to inhibit or induce the activity of metabolic enzymes. The aim of this study was to investigate the potential of the crude aqueous extracts of three popular medicinal herbs used in South Africa to inhibit major cytochrome P450 (CYP) enzymes. Material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
(21 reference statements)
0
13
0
Order By: Relevance
“…Natural products owing to their low-toxicity have been increasingly developed and used as antitumor drugs (Fasinu et al, 2014). Regarding the efficacy and safety of the herbal medicines, several concerns have also been raised, such as biotransformation of the drug, drug-drug interaction et.al.…”
Section: Discussionmentioning
confidence: 99%
“…Natural products owing to their low-toxicity have been increasingly developed and used as antitumor drugs (Fasinu et al, 2014). Regarding the efficacy and safety of the herbal medicines, several concerns have also been raised, such as biotransformation of the drug, drug-drug interaction et.al.…”
Section: Discussionmentioning
confidence: 99%
“…The use of medicinal herbs, a principal component of traditional medicine, predates the emergence of HIV/AIDS, and there is widespread consumption of herbal products for the management of HIV/AIDS either as complementary or alternative medicine [29].…”
Section: Discussionmentioning
confidence: 99%
“…However, the popularity of this plant rose tremendously following the increased [32] that is hydrolyzed into rooperol in the large intestine [33]. Pharmacokinetic studies have indicated that rooperol can be found in feces, and metabolites are found in the serum and urine as its glycosides, sulfates, mixed glucuronides and sulfuronides [29]. The glycoside has low toxicity and the corm containing it is also used as food [30] and has been well used for traditional and pharmaceutical purposes [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing practice of co-administering herbal medicines with conventionally prescribed medications has raised considerably the risk of potential drug-herb interactions, especially in patients who already are on complex treatments involving narrow therapeutic index drugs [ 1 , 7 , 8 ]. Pharmacokinetic herb-drug interactions are one of the major risks caused by phytochemicals modulating the activities of enzymes that metabolize drugs, which subsequently affects their bioavailability [ 9 ]. For example, St. John's wort can decrease the steady state plasma concentrations of cyclosporine, midazolam, tacrolimus, amitriptyline, digoxin, indinavir, warfarin, phenprocoumon, and theophylline [ 10 ].…”
Section: Introductionmentioning
confidence: 99%